MODEL PEMBELAJARAN PJBL BERBANTUAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS DAN LITERASI SAINS PESERTA DIDIK: LITERATUR REVIEW SISTEMATIS - Nafingah, Hanim; Ekawati, Ratna; Faizah, Siti (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Critical thinking skills and science literacy are very important abilities and are needed by students in the 21st century era. Critical thinking skills and science literacy are one of the benchmarks of high and low human resources so they need to be developed for students since they are at the basic education level. This research aims to conduct a literature review to examine the influence of the Problem-Based Learning (PBL) model assisted by animated video media on enhancing students' critical thinking skills and scientific literacy. The research method employed in this study is Systematic Literature Review literacy in elementary school.